Assimilation of Handwriting Model Comenia Script with the Educational Process of Primary School - Fasnerova, Martina (Civilia, 2016)
Since 2010, the primary school pupils to submit further written draft, under the name Comenia Script. In this connection it was implemented as supporting research aimed at assimilation handwriting model Comenia Script to Czech schools. The chapter will describe the positives and negatives of the new originals written and its adaptation to teaching the Czech language with regard to the development of literacy of primary school pupils. Due to the potential variability of individual graphemes while practicing writing with writing the draft Comenia Script happens that the written text becomes sometimes difficult for students to read backwards. In such cases are pupils limited, (disadvantaged) obtaining information from the text, which is technically not read properly.
Keywords: Handwriting model; Joined-up linear handwriting; Comenia Script; Primary education; Primary school; Educational process; Pupil literacy